-(3-2n)+7=3(n+3)

Simple and best practice solution for -(3-2n)+7=3(n+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(3-2n)+7=3(n+3) equation:



-(3-2n)+7=3(n+3)
We move all terms to the left:
-(3-2n)+7-(3(n+3))=0
We add all the numbers together, and all the variables
-(-2n+3)-(3(n+3))+7=0
We get rid of parentheses
2n-(3(n+3))-3+7=0
We calculate terms in parentheses: -(3(n+3)), so:
3(n+3)
We multiply parentheses
3n+9
Back to the equation:
-(3n+9)
We add all the numbers together, and all the variables
2n-(3n+9)+4=0
We get rid of parentheses
2n-3n-9+4=0
We add all the numbers together, and all the variables
-1n-5=0
We move all terms containing n to the left, all other terms to the right
-n=5
n=5/-1
n=-5

See similar equations:

| 16.4+2x=7.5+7.5x | | 8+11x=140 | | -(1y+8)-5=4(y+2)-6y | | x-42=76 | | |9-3n|=3 | | x-40=-63 | | 70-x=4 | | 14-w=16 | | x+57=16 | | 2x2+19x+40=-2x | | 6x+7=26,1 | | 6-4x=-2x-6 | | 4=5x=-41 | | 6-4x=2x-7 | | 4d−6=30d= | | -3x+4=18-5x | | -6=3x=-39 | | 21=5v-2v | | -7x+9=75 | | 18+x=94 | | -7x=9=-75 | | 5x−3=15 | | 2.25n=90,n | | 10x+33=100 | | 5x−3=15, | | 6x+7(4x+6)=-94 | | 2x−110=390. | | 2x+7/3=8,7 | | -4(-x-5)=42 | | t/3−22=-13 | | 5x-8 = 14 | | w=-1+1/5 |

Equations solver categories